2016
DOI: 10.1002/jbm.b.33805
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of surface modification by electrochemical deoxidation: Effect on surface characteristics and initial bioactivity of zirconia

Abstract: The aim of this study was to investigate and compare the surface characteristics and initial bioactivity of ceria-stabilized zirconia/alumina nanocomposite (NANOZR) with those of yttria-stabilized zirconia (3Y-TZP) and pure titanium (CpTi) following the use of three surface modification methods; polishing, sandblasting/acid-etching (SB-E) and electrochemical deoxidation (ECD). Physical properties including surface morphology, chemical composition, X-ray diffraction, surface wettability, surface roughness, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The handling process is simple and safe because of the lack of harmful emitted vapors. Liu et al showed that zirconia-particle coating led to a shear bond strength superior to that of tribochemical silica coating, glazing porcelain coating after sintering of zirconia, and silica slurry coating prior to the sintering of zirconia after thermocycling [42]. The increase in Ra in the present study from 60.08 nm (control) to 164.765 nm shows that use of the slurry produces excellent results.…”
Section: Discussionsupporting
confidence: 51%
“…The handling process is simple and safe because of the lack of harmful emitted vapors. Liu et al showed that zirconia-particle coating led to a shear bond strength superior to that of tribochemical silica coating, glazing porcelain coating after sintering of zirconia, and silica slurry coating prior to the sintering of zirconia after thermocycling [42]. The increase in Ra in the present study from 60.08 nm (control) to 164.765 nm shows that use of the slurry produces excellent results.…”
Section: Discussionsupporting
confidence: 51%
“…For example, electrochemical deoxidation of zirconia (ECD) improved its biocompatibility by developing a micro-porous surface and thus lowering the contact angle. This method is known to enhance surface wettability through oxygen removal from the surface of the solid zirconia using molten salt electrolysis [63].…”
Section: Electrochemical Treatmentmentioning
confidence: 99%
“…However, zirconia has a limitation in electrochemical application because of its non-conductive character. Liu et al (60) introduced the electrochemical deoxidation (ECD) technique to improve zirconia surfaces, which removed oxygen from the solid metal oxides via molten salt electrolysis. It suggested that ECD treated zirconia showed well-arranged microporous, low contact angles, and a slight decrease in monoclinic phase content (−4.4 wt%).…”
Section: Electrochemical Treatmentmentioning
confidence: 99%